2005
DOI: 10.1002/eji.200535421
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐induced TNFR family‐related protein (GITR) activation exacerbates murine asthma and collagen‐induced arthritis

Abstract: Glucocorticoid‐induced TNFR family‐related protein (GITR) is expressed at low levels on resting T cells, B cells and macrophages but at high levels on regulatory T cells (Treg). Although GITR expression is up‐regulated on CD4+ effector cells upon activation, the role of GITR in Th1 and Th2 cell development is unclear. We report here that activation of GITR signalling by anti‐GITR antibody markedly enhanced the induction of both Th1 and Th2 cytokine production by naive CD4+CD25– T cells. Consistent with this ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 22 publications
11
70
1
Order By: Relevance
“…Our results obtained from pups treated with DTA-1 after OVA sensitization confirmed that GITR ligation in an inflammatory context (as a costimulatory signal) exacerbates allergic airway disease (37). In contrast, GITR ligation alone, in naive animals (not as a costimulatory signal) has little effect on inflammatory responses (32,55).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results obtained from pups treated with DTA-1 after OVA sensitization confirmed that GITR ligation in an inflammatory context (as a costimulatory signal) exacerbates allergic airway disease (37). In contrast, GITR ligation alone, in naive animals (not as a costimulatory signal) has little effect on inflammatory responses (32,55).…”
Section: Discussionsupporting
confidence: 72%
“…This costimulatory function of GITR signal may explain the exacerbation of asthma when DTA-1 mAb were injected in OVA-sensitized pups (37). However, we assume that DTA-1 mAb injected in 4-day-old naive pups had a different effect, because in these offspring IFN-␥, IL-4 (serum), and IL-10 remained at (or were reduced to) low levels when the pups were submitted to suboptimal asthma induction.…”
Section: Discussionmentioning
confidence: 96%
“…Murine and human IL-33 proteins were either produced in-house (18,24) or obtained from PeproTech with similar results.…”
Section: Recombinant Il-33mentioning
confidence: 99%
“…qPCR qPCR was conducted as described previously (24,25) with specific probe/ primer or primer sets for arginase I (Mm01190441_g1; Applied Biosystems), r18S (Applied Biosystems), CCL-5 (Mm01302427_m1; Applied Biosystems), ST2L (18), Ym1 (forward, catgagcaagacttgcgtgac; reverse, ggtccaaacttccatcctcca; Invitrogen), and iNOS (forward, cagctgggctgtacaa acctt; reverse, cattggaagtgaagcgtttcg; Invitrogen).…”
Section: Flow Cytometry and Facsaria Sortingmentioning
confidence: 99%
“…In addition to T-bet, SLAM can induce expression of Stat1 and NF-κB (Quiroga et al, 2004), i.e., transcription factors that may also play a role in the activation of the IFN-γ gene. Furthermore, T-bet is induced by the co-stimulatory receptors GITR (Patel et al, 2005) and Sema4a (Kumanogoh et al, 2005), as well as by the signal transducer p38 Mitogen-Activated Protein (p38MAP) …”
Section: Induction Through Costimulatory Factorsmentioning
confidence: 99%